An Introduction to Sizing Centrifugal Pumps in Aquaculture - Jordan Neff; J. A. Watson; W. A. Porter (EDIS)
This publication explains the basic methodology used to size pumps for aquaculture systems; however, these concepts can be applied to a variety of pumping systems. Written by Jordan Neff, J. A. Watson, and W. A. Porter, and published by the UF/IFAS Department of Agricultural and Biological Engineering, September 2022.